Decision support of a developer in residential project preparation - Bucoń, Robert (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Preparation of a residential project in accordance with the expectations of a buyer requires from a developer a lot of experience and a good knowledge of housing market. Preferences of people looking for flats are very diverse, therefore, it is essential to know the factors which are taken into consideration when buying a flat. The level of flats sale and income gained from it depend on how much the offered flats meet the requirements of buyers. Understanding the flats buyers’ preferences requires a detailed study among potential buyers that aims at identifying the factors taken into consideration while choosing a flat and determining their influence on the made decision. In the article, the method is presented which supports a developer in making decisions regarding the development of a building concept in relation to design and material solutions, its location and making the offers of flats for sale more attractive.